(untitled) (Journal of Pakistan Orthopaedic Association, 2023)
Background: The total hip arthroplasty (THA) procedure is effective surgical procedures of twentieth century. THA has been considered using a variety of techniques. The objective of current study was to determine outcome of Piriformis muscle sparing (PSM) posterior approach in total hip replacement. Materials and Methods: This cohort study was carried out in Institute Of Orthopaedics & Surgery and South City Hospital Karachi. The study includes total 60 patients that underwent THA. Piriformis-sparing posterior approach procedure was performed. Outcome was assessed before procedure and at 2 weeks and 6 weeks, 3 months and 1 year postoperatively. Pain was assessed visual analogue scale (VAS).The Oxford Hip Score (OHS) and 12-item Short Form Survey (SF-12) were applied to evaluate pain and hip function, respectively. Results: Mean BMI of the patients was 27.5±4.7, Mean pain score on VAS was 6.2±1.5 and OHS score was 20±8.After 1 year of procedure. Mean pain score on VAS was decreased to 1.2±0.5 and mean OHS score was 44±4.9 out of total score of 48, mean SF-12 PCS was 40.2±12.2, mean SF-12 MCS was 56.6±11.3. Conclusion: Piriformis muscle sparing posterior approach in Total Hip Replacement has better functional outcome in terms of postoperative pain and hip function. Piriformis muscle is very important for the hip function, so it should be saved whenever possible to get the best results after Total hip replacement with posterior approach